Anatomical analysis of the lizard carpal bones in the terms of skilled manual abilities - Fontanarrosa, Gabriela (2013)
One of the most remarkable hand movements is grasping. This ability has been repetitively associated with the evolution of the human lineage towards the development of technology. Besides mammals, other tetrapods have also evolved significant, and in some cases surprising, forelimb prehensile capabilities. In this study, we present a qualitative analysis of the carpal bones in diverse lizard taxa. Our main goal is to make a survey of the carpal morphology of different squamatans and to interpret its variability in the context of both lizard skilled forelimb movements and the evolutionary history of Squamata.